Assessment of the health impact of tanning industrial effluent in Kasur, Pakistan - Rahman, Muhammad Atiq ur; Morishita, Hideharu; Routray, Jayant Kumar; Takizawa, Satoshi; Tewari, Vinod K; Government of Japan (Bangkok : Asian Institute of Technology, 1997)
Kasur is a city whose name has become inextricably linked with the tanning industry that has existed there for several years. Income from tanning industry is ranked third in Pakistan's exports and tanneries in Kasur are the second highest contributor to that income, following the industry in Karachi with highest contribution. Due to lack of consideration for the environment, the effluents from tanning industry are adversely affecting human life, agriculture and livestock in Kasur. The residents, especially the tannery workers and the child labour, have been the victims of this pollution which has lead to ailments such as eye diseases, skin irritations and gastrointestinal problems. Chromium, extensively used in tanning process, is carcinogenic and cancer was reportedly found as cause of death in some cases. Organisations ranging from local government and NGOs to that belonging to federal government and international institutions have been trying to improve the environmental conditions of Kasur. These efforts, however, have been unsuccessful because of the difficulties encountered in increasing the level of environmental understanding in the society. To solve this problem, it is necessary to communicate the severity of the situation to citizen, government and industry. The aim of the study is to clarify the relationship between the health condition of the residents and the activities of industries to increase public awareness on the issues related with environmental risk assessment and management in Kasur.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science. School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1997
Keywords: Industrial hygiene -- Pakistan -- Kasur